The Effect of School Image on Students’ Loyalty with Satisfaction as Mediating Variable on Private Secondary Schools with Different Social Class - Febrine Pentadini; Retno Yustini Wahyuningdyah (Soegijapranata Catholic University, 2022)
Student’s loyalty is needed to promote the school. Some factors that affect loyalty are school image and satisfaction. This study aims at analyzing the effect of school image to the students’ loyalty with satisfaction as mediating variable and testing if there is the different effect on private secondary students with different social class. Questionnaires to 126 students from two different social classes were collected. Multiple regression linear and Sobel test were applied to see mediating effect of satisfaction. The results indicate that school image gives small effect on students’ loyalty but higher effect on students’ satisfaction. There is no different effect to the students’ loyalty from different social class.